Study of heavy metal in sediment of The Klagison River, Sorong City - Nurbia, Nurbia; Affandi, Samsuddin (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
The Klagison River is one of the rivers located in the North Sorong District to the Sorong Manoi District. The flow of the Klagison River is used by the sand mining industry to dispose of liquid waste products from mining sites. Mining activities are in the middle of the Klagison River so that it can affect the quality of river water and experience a decrease in carrying capacity due to the high level of turbidity in river water caused by sedimentation. The purpose of this research is to provide knowledge about the content of metal elements in sediments by identifying the constituent elements of the Klagison River sediments, Sorong City, West Papua. Determination of the sampling point using the purposive sampling method and the sediment collection tool using the Ekman grab. The method of analyzing the constituent elements of the sediment uses the XRF (X-Ray Fluorescence) method. Based on the research results, there are various types of metal elements contained in the sediments of the Klagison River, namely the elements Al, Si, P, S, Cl, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, Rb, Sr, Zr and Re where the dominant concentration of metal elements from 5 observation stations is Fe>Si>K>Cl>Al>Ca. At the 5 observation stations, the element Fe>Si>K>Cl>Al>Ca was the highest compared to the other 4 observation stations. This is because station 5 is the mouth of the Klagison River so that it becomes a place for liquid waste deposits to coalesce.